2016
DOI: 10.1007/s11605-015-3052-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary Gastrointestinal Non-Hodgkin’s Lymphoma of the Small and Large Intestines: a Systematic Review

Abstract: The majority of patients with non-follicular small and large intestinal PGINHLs are treated with both chemotherapy and surgery. Although surgery appears to be an important part of the treatment algorithm, definitive statements regarding its survival benefit remain limited due to lack of patient stratification based on timing and indication for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
71
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 54 publications
5
71
2
4
Order By: Relevance
“…It is fairly considered to be acceptable as compared with other many recent studies that reported the 5 years survival rate is (52-86%), considering our results performed in a small number of cases and during less follow up period. 16 Additionally, we observed that 2/3 of total deaths had acute complications, necessitating urgent laparotomy and this is consistent with Lightner et al, who noticed that urgently operated patients with primary intestinal lymphoma carried poor prognosis. 16 These variations in the results of surgical outcome of our series in comparison with other studies may be due to difference in patient's clinical criteria, tumor size and location, histopathologic subtype, in addition to the available facilities of early diagnosis.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…It is fairly considered to be acceptable as compared with other many recent studies that reported the 5 years survival rate is (52-86%), considering our results performed in a small number of cases and during less follow up period. 16 Additionally, we observed that 2/3 of total deaths had acute complications, necessitating urgent laparotomy and this is consistent with Lightner et al, who noticed that urgently operated patients with primary intestinal lymphoma carried poor prognosis. 16 These variations in the results of surgical outcome of our series in comparison with other studies may be due to difference in patient's clinical criteria, tumor size and location, histopathologic subtype, in addition to the available facilities of early diagnosis.…”
supporting
confidence: 91%
“…However, the incidence of the disease has been increasing by 5% per year in Westernized countries, peaking at 1.73 per 100.000 in North America. [14][15][16] In this study the mean age at time of presentation is 46±32 year this is near to what reported by different groups. 10,12 Primary intestinal lymphoma usually affects males than females.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations